Analyzing volatiles in brown rice vinegar by headspace solid-phase microextraction (SPME)–Arrow: Optimizing the extraction conditions and comparisons with conventional SPME. Issue 1 (1st January 2019) - Nam, Tae Gyu; Lee, Jun-Young; Kim, Bum-Keun; Song, Nho-Eul; Jang, Hae Won
ABSTRACT: The ability to readily determine the composition of brown rice vinegar is important for quality assurance purposes. To that end, solid–phase microextraction (SPME)–Arrow method was optimized for the determination of volatile organic compounds (VOCs) from brown rice vinegar. Compared to traditional SPME fibers, SPME–Arrow has a larger sorbent-phase volume and is more durable. The SPME–Arrow conditions, including coating material, extraction temperature, extraction time, and NaCl concentration, were examined, which led to optimum extraction conditions that include: carboxen/polydimethylsiloxane (CAR/PDMS) fiber, 50°C, 30 min of SPME–Arrow, and 0% NaCl (i.e., no added NaCl). The developed method was compared to an optimized method based on conventional SPME. Twelve major VOCs, including acetates, alcohols, aldehydes, acids, and furan derivatives, were extracted by SPME–Arrow, while only seven VOCs were extracted using the traditional SPME. Moreover, SPME–Arrow extracted more 1.3–2 times more VOCs than SPME. Hence, the CAR/PDMS SPME–Arrow fiber is suitable for acquiring VOC profiles from brown rice vinegar.